Religiöse Sozialisation in muslimischen Familien -- Eine vergleichende Studie - Uygun-Altunbas, Ayse (Globaler lokaler Islam, 2017)
How is religion imparted and lived in Muslim families? And what parts do other facilities of socialization, such as mosques, schools or even the media, play in religious education?